PENGARUH KUALITAS AUDIT TERHADAP MANAJEMEN LABA - Muhammad Dody Amijaya; Andri Prastiwi (Diponegoro Journal of Accounting, 2013)
Earnings management is an action taken to regulate managers profit by raising, lowering and flattening income managers as you wish, so as to reduce the credibility of financial statements. With the earnings management, it will increase agency costs. To reduce agency costs will require a qualified auditor who acts as a controller such as the size of the Firm, Auditor industry specialist, and auditor independence. Therefore high quality audits which acts as an effective deterrent earnings management, because management's reputation will be destroyed and the value of the company will go down if this false reporting detected or uncovered. The samples used in this study is a banking company listed in Indonesia Stock Exchange in 2008-2011. Results indicate that audit quality is measured by the size of the firm and industry specialist auditors negatively affect earnings management. So that the existence of the firm size and industry specialist auditors can inhibit earnings management. While the existence of the independence of auditors failed to prove capable of limiting earnings management.